Business Intelligence Implementation To Analyze Perfect Store Data Using the OLAP Method - Maulana, Afik; Wulandari, Dewi Ayu Nur (Sinkron : jurnal dan penelitian teknik informatika, 2019)
Perfect store is one of the business strategies owned by PT. Unilever where a store provides an appropriate product assortment and ensures visibility by displaying products in accordance with the planogram, and placed in the right position by taking into account the habits of the buyer and using the right display tools. This perfect store strategy aims to increase sales in the context of business development. To find out whether the perfect store strategy has been applied in all existing areas, a perfect store audit is needed. The method used to audit perfect store data is OLAP (Online Analytical Processing). The results of data processing with OLAP are in the form of a perfect store audit report that is accurate, relevant and timely which is presented in the form of an analysis chart that will be used by PT. Uniliver to see which areas have increased sales from the perfect store strategy that has been implemented so that PT Uniliver can determine the right marketing strategy.